Decreased Heparin Sensitivity of Cyclohexanedione-Modified Factor Xa - Blaskó, György; Machovich, Raymund (Thrombosis and Haemostasis, 1979)
Modification of 12 arginine residues of bovine Factor Xa with 1,2-cyclohexanedione has resulted in a decrease in heparin sensitivity of the reaction between enzyme and antithrombin-III, whereas the antithrombin-III sensitivity of modified Factor Xa was only slightly affected. It is suggested that heparin accelerates the Factor Xa-antithrombin-III reaction by interacting with Factor Xa.